NURSES’ SLEEP QUALITY AND QUALITY OF LIFE DURING THE COVID-19 PANDEMIC: ANALYSIS OF CORRELATION AND DIFFERENCES IN THE RAJAWALI ISOLATION AND NON-ISOLATION WARDS - Nurhasanah Nurhasanah; Hang Gunawan Asikin; Natalia Dewi Wardani; Widodo Sarjana; Witrie Sutaty Miliawati Rahayu (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: Nurses are one of the first-line fighters who treat Coronavirus disease 2019 (COVID-19) patients. They are prone to stress, anxiety, and sleep disturbances that can interfere with nurses providing medical services. Although some clinical research has established sleep quality and quality of life, the comparisons of sleep quality, quality of life, and each domain of quality of life for nurses who work in isolation and non-isolation wards is not well knownObjective: This study examines the correlation between sleep quality and quality of life amongst Dr. Kariadi General Hospital nurses during the COVID-19 pandemic.Methods: This quantitative study uses a cross-sectional approach. 51 nurses who worked in the Rajawali rooms in the isolation and non-isolation wards for COVID-19 at Dr. Kariadi Semarang were included by the consecutive sampling method. The instrument used are the sociodemographic questionnaire, The PSQI, and The WHOQOL-BREF Indonesian versions. Bivariate analysis was analyzed using the Spearman testResults: There was a correlation between sleep quality and the quality of life of nurses (p=0.020,r= -0.325). There was a difference between the sleep quality of nurses who work in isolation and non-isolation wards (p=0.03). There was no difference between the quality of life of nurses who work in isolation and non-isolation wards (p = 0.698).Conclusion: There is significant correlation between nurses’ sleep quality and their quality of life. There’s bad quality of life for nurses who worked inward isolation so further examination and periodic screening are needed to optimize their care.